Ulos Batak Toba: Makna Religi dan Implikasinya pada Peradaban dan Estetika - Tinambunan, Edison R.L. (Sekolah Tinggi Teologia dan Filsafat Widya Sasana, 2023)
This research is discussing Toba Batak ulos whose application has been widely spread, not only among Batak tribes but also all over Indonesia and worldwide; especially since Hutaraja Ulos Village, Samosir Region, North Sumatra was launched. With the use of qualitative methodology, a phenomenological approach is used to find out the religious meaning of Toba Batak ulos which is integrated in garnish, colors, and the weavers. The garnish of ulos refers to the intention of the application of ulos so that it meets the wish of the giver and receiver of the ulos in accordance with its bestowed religious meaning. The colors of ulos which intrinsically flow on each ulos yeast symbolize the presence of God. The weaver as the creator of the ulos is also envisioning ulos religiosity. The transformation of ulos religiosity is revealed in the social culture which indicates the civilization concerning Toba Batak traditions and customs. Moreover, ulos religiosity is also affirmed in fashion aesthetics which has been implemented from the very beginning of the creation of ulos up to these days: we have to wear, implement, appreciate, and honor the virtues in our lives. Obviously, Toba Batak ulos has high religious and social values to unite the divine–man, man-divine, and man-man dimensions.